동영상 교육이 대장내시경 대상자의 장 정결 이행에 미치는 영향 - 조유영; 김현옥; Cho, You Young; Kim, Hyeon Ok (Journal of Korean Academy of Nursing, 2015)
Purpose: The purpose of this study was to evaluate the effects of an educational video program on bowel preparation for a colonoscopy. Methods: The study used a non-equivalent control group and non-synchronized design as a quasi-experimental research involving 101 participants undergoing bowel preparation for a colonoscopy (experimental group 51, control group 50 subjects) at W. university hospital, from Aug. 7 to Oct. 31, 2013. The control group received verbal education with an explanatory note while the experimental group received education using a video program. To measure knowledge of diet restrictions and compliance with ingesting bowel preparation solutions, a questionnaire, based on The Korean Society of Gastrointestinal Endoscopy's Guide (2003), developed by Sam-Sook You, was used after revisions and supplementation was done. To measure bowel cleanness, the 'Aronchick Bowel Preparation Scale' was adopted. Data were analyzed using the SPSS WIN 12.0 program. Results: A higher proportion of the experimental group showed a positive change in knowledge level on diet restrictions (U=1011.50, p =.035) and ingestion of bowel preparation solutions (U=980.50, p =.019), a higher level of compliance with diet restrictions (U=638.50, p <.001), ingesting bowel preparation solutions (U=668.00, p <.001) and the level of bowel cleanness (${χ}^2$=17.00, p <.001) than the control group. Conclusion: The results of this study indicate that a video educational program for patients having a colonoscopy can improve knowledge, level of compliance with diet restrictions, ingestion of bowel preparation solutions, and bowel cleanness. Therefore video educational program should be used with this patient group.